2018
DOI: 10.1111/ipd.12354
|View full text |Cite
|
Sign up to set email alerts
|

Does flavoured dentifrice increase fluoride intake compared with regular toothpaste in children? A systematic review and meta‐analysis

Abstract: There is evidence to support the null hypothesis that flavouring from dentifrice does not increase fluoride intake in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Children are tempted to use the flavoured fluoridated toothpastes and many of them swallow them frequently, and in that way these children are at risk of developing detrimental health effects both in teeth and in bones due to the excess ingested fluoride. 19 Bentley et al 20 reported that 0.42 mg fluoride was ingested when 1450 mg/l fluoride toothpaste is used and 0.10 mg ingested when using toothpaste with 400 mg/l fluoride. Current recommendations suggest that for a child with a low caries risk a smear or pea sized amount of toothpaste containing a minimum of 1000 ppm fluoride is recommended for use, and not 500 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children are tempted to use the flavoured fluoridated toothpastes and many of them swallow them frequently, and in that way these children are at risk of developing detrimental health effects both in teeth and in bones due to the excess ingested fluoride. 19 Bentley et al 20 reported that 0.42 mg fluoride was ingested when 1450 mg/l fluoride toothpaste is used and 0.10 mg ingested when using toothpaste with 400 mg/l fluoride. Current recommendations suggest that for a child with a low caries risk a smear or pea sized amount of toothpaste containing a minimum of 1000 ppm fluoride is recommended for use, and not 500 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…17 if a person has a low to moderate level of caries, that is, decayed, missing or filled teeth (DMFT) fewer than 3, organisations such as the wHO, British Dental Association, royal College of Surgeons of england and Scotland, NiCe and the American Dental Association recommend the use of a fluoridated toothpaste containing 1350-1500 mg/l fluoride, but a high-caries risk patient (DMFT more than 5) is recommended to need 2800 or even 5000 ppm fluoride. 19,20 india does not have an evidencebased valid recommendation of fluoride supplementations. This needs addressing as there are several fluorosisendemic areas in the country, and there are fluoride-deficient areas as well.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] Current evidence suggests that there are statistically insignificant differences in F ingestion between <1000 ppm F and ≥1000 ppm F dentifrice, regardless of flavour. 18,19 Current evidence, however, suggests superior efficacy of ≥1000 ppm F dentifrice compared with <1000 ppm F dentifrice in reducing dmft increments in the primary dentition, 10 which has been reflected in paediatric dental guidelines in other world regions. 20 Therefore, these F concentrations levels were used to categorise dentifrice types in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There, however, are concerns about F ingestion in young children, 12‐14 due to their limited ability to expectorate dentifrice 15‐17 . Current evidence suggests that there are statistically insignificant differences in F ingestion between <1000 ppm F and ≥1000 ppm F dentifrice, regardless of flavour 18,19 . Current evidence, however, suggests superior efficacy of ≥1000 ppm F dentifrice compared with <1000 ppm F dentifrice in reducing dmft increments in the primary dentition, 10 which has been reflected in paediatric dental guidelines in other world regions 20 .…”
Section: Discussionmentioning
confidence: 99%
“…15,20,23 However, according to a systematic review, there is evidence that flavored toothpaste does not increase fluoride intake in young children. 27 Parents should be aware that fluoride dentifrice is considered a medicine, a preventive and a therapeutic agent against caries and should not be available to the child. [6][7]21 It is worth noting that ingestion of a "pea-sized" amount or more of fluoride dentifrice can lead to risk of developing mild dental fluorosis.…”
Section: Discussionmentioning
confidence: 99%